Six‐Year Survival of a Mini Dental Implant‐Retained Overdenture in a Child with Ectodermal Dysplasia. Issue 1 (29th September 2015) - Kilic, Serdar; Altintas, Subutay Han; Yilmaz Altintas, Nuray; Ozkaynak, Ozkan; Bayram, Mehmet; Kusgoz, Adem; Taskesen, Fatih
Abstract: Patients with ectodermal dysplasia (ED) experience several problems caused by abnormal development and functioning of the head and neck region. In addition to developmental nasal cartilage abnormalities and absence of sweat glands, hair, and eyebrows, edentulism or developmental disorders of teeth (cone‐shaped teeth) are commonly observed in these types of patients. ED is also characterized by underdeveloped alveolar ridges, a decreased occlusal vertical dimension, reduced salivary secretion, and dry oral mucosa, which make prosthetic rehabilitation difficult. Few studies of intraosseous dental implant‐retained prostheses have described adverse effects on craniofacial growth and esthetic and functional disadvantages, while some researchers have described the advantages of this treatment option as an alternative option in these cases. Due to the associated alveolar bone deficiency, dental mini‐implant therapy may be a treatment option for these patients; however, there are isolated cases in the literature regarding the rehabilitation of ED patients with mini‐implant‐supported overdentures. This clinical report describes the rehabilitation of a 6‐year‐old child with ED using a maxillary removable partial prosthesis and a mini‐implant‐retained mandibular overdenture. The clinical and radiographic findings of this prosthetic rehabilitation during the 6‐year follow‐up are also presented.